Traumatic Blunt Force Renal Injury in a Diseased Horseshoe Kidney with Successful Embolization to Treat Active Bleeding: A Case Report and Literature Review. (25th July 2020) - Krutsri, Chonlada; Singhatas, Pongsasit; Sumpritpradit, Preeda; Chaijareenont, Chunlaches; Viseshsindh, Wit; Thampongsa, Tharin; Choikrua, Pattawia
Abstract : Background . Blunt force injuries in patients with preexisting kidney disease account for 19% of all kidney injuries, suggesting that diseased kidneys are more vulnerable than normal kidneys. When a horseshoe kidney (a rare anomaly: prevalence of 0.2%) is injured, treatment is challenging, especially when nonoperative management is desired. In high-grade blunt force normal kidney injury, nonoperative management has high succession rate (94.8%) with kidney-related complication (13.6%). Surgical reconstruction and preservation of a damaged horseshoe kidney is difficult because of variations in its vascular anatomy. We report successful nonoperative management of a blunt horseshoe kidney injury with active bleeding and review previous outcomes and complications. Case Presentation . A 57-year-old man had a head-on collision motorcycle road traffic accident. On arrival, blood pressure was 90/60 mmHg, pulse rate 140 bpm, and clear yellow urine output 200 ml. The patient was transiently responsive to fluid and blood component. Whole body computed tomography showed a high-volume retroperitoneal hematoma and multiple-lacerated lower pole of the kidney, compatible with preexisting horseshoe kidney disease with active contrast-enhanced extravasation from the accessory right renal artery. Embolization was performed. Renal function, transiently impaired after embolization, normalized on day 3. An infected hematoma found on day 7 was successfully controlled with antibiotics. His recovery was uneventful. At the 6-month follow-up, his serum creatinine level had returned to normal. The average age of blunt force horseshoe kidney injury is 31.75 years and occurred more common in male (87.5%). Conclusion . Diseased horseshoe kidneys are prone to injury even with low-velocity impact such as a road traffic accident speed < 15 km / h . Embolization is considered the first choice for management, with its high clinical success rate leading to less need for surgical repair. Not removing a hematoma is likely to result in complications. If embolization fails to stop bleeding, life-saving surgical exploration should be mandated.